Liberalisation of agricultural trade and net social welfare: a study of selected crops - Ramesh Chand (1999)
This study quantifies the impact of globalisation on producer surplus, consumer surplus and net social welfare for four crops - rice, maize, chickpea and rapeseed-mustard. This would help in formulating commodity-specific policies on pricing, production, tariffs and trade. The study finds that while the impact of globalisation would vary from commodity to commodity, there is scope for increasing its benefits by reducing domestic marketing costs and tapping better suppliers for imports. - Reproduced
Keywords: Agricultural products